Simultaneous Endovascular Repair Is Not Associated With Increased Risk for Thoracic and Abdominal Aortic Pathologies: Early and Midterm Outcomes - Zhang, Weichang; Zhang, Lei; Li, Xin; Li, Ming; Qiu, Jian; Wang, Mo; Shu, Chang (Frontiers in Cardiovascular Medicine, 2022)
Coexisting multilevel aortic pathologies were caused by atherosclerosis and hypertension and presented in a small subgroup of patients. Endovascular repair is a safe and effective treatment for a variety of aortic pathologies. However, fewer small series and cases were reported using simultaneous thoracic endovascular repair (TEVAR) and endovascular aneurysm repair (EVAR) for both aortic segments. To determine the outcomes of simultaneous and separately TEVAR and EVAR treating for multilevel aortic pathologies. Between 2010 to 2020, thirty-one patients and twenty-one patients were treated by one-staged and two-staged repair at a single center. All patients had the concomitant thoracic and abdominal aortic disease (aortic dissection, aneurysms, penetrating aortic ulcers). Compared with the patients with two-staged aortic repair, one-staged repair patients were older (mean age, 68 vs 56 years; P < .001) and had a larger preoperative maximal aortic diameter (67.03±10.65 vs 57.33±10.60 mm; p = .0022). The intraoperative and postoperative outcomes show that the procedure times and length of hospital stay (LOS) were longer in the two-staged group. There is no significant difference in postoperative complications between the two groups. In follow up, the freedom from re-intervention and the mean survival time estimates for one-staged and two-staged group were 100% vs 100%, 92.4% vs 95%, 88% vs 88%, 90.5% vs 90.5%, 87% vs 90.5%, 76% vs 84%, at one, two, and five years, respectively, with no statistics difference. Combined TEVAR and EVAR can be performed successfully with minimal morbidity and mortality. The one-staged repair was not associated with the increased risk for multilevel aortic pathologies treatment.